2019
DOI: 10.1080/03066150.2019.1632294
|View full text |Cite
|
Sign up to set email alerts
|

Gender, politics and sugarcane commercialisation in Tanzania

Abstract: This article explores relationships between state, corporate capital and local stakeholders in the political economy of sugarcane from a gender perspective. The findings, based on empirical research at the site of Tanzania's largest sugarcane producer pre-and post-privatisation, provide insights into the degree to which the estateoutgrower model can be regarded as 'inclusive' for women and men. Three aspects of commercial sugarcane production are analysed: land tenure, labour and leadership within canegrowers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Choudhury et al, 2020 , Ferrando and Vecchione-Gonçalves, 2020 , Guevara Gil and Cabanillas Linares, 2020 , Nabarro et al, 2020 , Ojeda and del Arco, 2020 , Sulle and Dancer, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Choudhury et al, 2020 , Ferrando and Vecchione-Gonçalves, 2020 , Guevara Gil and Cabanillas Linares, 2020 , Nabarro et al, 2020 , Ojeda and del Arco, 2020 , Sulle and Dancer, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Due to their different social roles, men and women do not equally experience the benefits and trade-offs of NREPs. Previous research suggests that women are disproportionately affected by the negative impacts (Eftimie et al 2009b;Muchadenyika 2015;Sulle and Dancer 2019; see also Hill et al 2021, Kimotho andOgol 2021, this volume). Evidence also shows that particularly in terms of socio-economic impacts (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Women's labour remains unremunerated, loses value, and becomes readily available as a l ow-cost input into projects of commercialization. Thus, studies of export-oriented agriculture have shown that investment schemes typically have created a l ow-paid, often seasonal, and disproportionately female labour force, although differentiated by other status positions ( Barrientos et al, 1999;Barndt, 2008;Bigler et al, 2017;Sulle and Dancer, 2020). Moreover, gendered inequalities, in intersection with other status positions, have facilitated the extraction of surplus value from agriculture, establishing ' chains of exploitation' with rural women at the bottom and agribusiness companies at the top ( Maffii, 2009;Luna, 2019).…”
Section: The Gendered Impacts Of Commercialization On Food Securitymentioning
confidence: 99%